Focal adhesion formation of primary human gingival fibroblast on hydrothermally and in-sol-made TiO2-coated titanium - Riivari Sini; Närva Elisa; Kangasniemi Ilkka; Willberg Jaana; Närhi Timo (WILEY, 2025)
Optimal cell adhesion of the gingival fibroblasts to dental implants is important for maintaining good implant integration. The aim of this study was to discover, if the nanoporous TiO2-coating on titanium alloy substrates is able to increase the cell adhesion of the human gingival fibroblasts (HGF). The study consisted of three differently produced titanium groups: hydrothermally produced TiO2-coating (HT), novel TiO2-coating made in sol (SOL), and noncoated control group. Primary HGF cells were initiated from gingival biopsies from patients having a third molar extraction. HGF were cultivated on titanium discs for 2 and 24 h to determine the initial attachment with confocal microscope. The cell spreading and adhesion protein signals were measured. In addition, expression of adhesion proteins vinculin, paxillin, and focal adhesion kinase (FAK) were measured after 3 days of cultivation by using Western Blotting. Higher protein levels of paxillin, vinculin, and FAK were induced on both coated discs compared to noncoated discs. The difference was statistically significant (p < 0.05) concerning expression of paxillin. The cell spreading was significantly larger on SOL discs after 2 and 24 h when comparing to noncoated controls. The confocal microscope analyses revealed significantly higher adhesion protein signals on both HT- and SOL-coated titanium compared to control group. This study showed, that both methods to produce TiO2-coatings are able to increase HGF adhesion protein expression and cell spreading on titanium surface. Accordingly, the coatings can potentially improve the gingival attachment to titanium implant surfaces.